Algal polysaccharides–Selenium nanoparticles regulate the uptake and distribution of selenium in rice plants - Yang, Chunmei; Wang, Chaoxin; Khan, Zaid; Duan, Songpo; Li, Zhiming; Shen, Hong (Frontiers in Plant Science, 2023)
Selenium (Se) is an essential trace element required for proper human and animal health. In this paper, we investigated the uptake and distribution characteristics of a new Se fertilizer, comprising of algal polysaccharides-selenium nanoparticles (APS-SeNPs), in rice plants with both hydroponics and pot experiments. The results from hydroponic experiments revealed that rice root uptake of APS-SeNPs fitted the Michaelis–Menten equation, and its Vmax was 13.54 μg g-1root dry weight (DW)h-1, which was 7.69 and 2.23 times that of selenite and selenate treatments, respectively. Root uptake of APS-SeNPs was inhibited by AgNO3 (64.81-79.09%) and carbonyl cyanide 3-chlorophenylhydrazone (CCCP) (19.83-29.03%), indicating that APS-SeNPs uptake by rice roots is mainly via aquaporins, and is also affected by metabolic activity. Moreover, sulfur deficiency caused rice roots to absorb more APS-SeNPs, and APS-SeNPs treatment increased the expression of the sulfate transporter OsSULTR1;2 in the roots, suggesting that OsSULTR1;2 is probably involved in the uptake of APS-SeNPs. APS-SeNPs application significantly increased the Se content in rice plants and the apparent Se uptake efficiency compared with selenate and selenite treatments. Most Se in the roots of rice plants was distributed in the cell wall, while Se was located primarily in the cytosol in shoots when treated with APS-SeNPs. Results from pot experiments indicated that Se application enhanced the Se content in each rice tissues, Noteworthy, the Se content in the brown rice under APS-SeNPs treatment was higher than that under selenite or selenate treatment and was mainly concentrated with in the embryo ends, and the Se was in organic form. Our findings provide important insights into the absorption mechanism and distribution of APS-SeNPs in rice plants.